THE STRUGGLE OF ISLAM AND CHRISTIANITY IN THE ESTABLISHMENT OF EDUCATIONAL INSTITUTIONS IN BOLAANG MONGONDOW, NORTH SULAWESI (1905-1942) - Mokodenseho, Sabil; Zamhari, Arif (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2021)
This study was conducted due to the scholars’ lack of attention in revealing the conditions of education in Bolaang Mongondow in the early twentieth century. Using historical methods, as well as sociological, religious, and political approaches, this study finds that in the early twentieth century, indigenous people received education through the Sarekat Islam's Islamic Education and Teaching Center and the Zending educational institution founded by Christian missionaries. Zending education for indigenous Muslim communities was a form of knowledge discrimination because education was only specifically for Christian children, European descent, and aristocrats, while indigenous Muslim children were not allowed. In contrast, Islamic educational institutions were established to accommodate all Muslim children. As a result, although Islamic education institutions existed long after the Zending educational institutions, their educational institutions can compete. Zending's education ended with the fall of Dutch rule, while Islamic educational institutions continue to exist to date. The differences between the two religions in managing educational institutions lead this paper to the conclusion that religion is important not only in responding to and positioning oneself in power relations but also in empowering individuals and groups.